Comparison of the solubilization of human platelet protein, cholesterol, gamma glutamyltransferase and lactate dehydrogenase by triton X-100 and Brij-35 - (:unkn) unknown (My University, 2003)
Triton X-100 and Brij 35 are nonionic polyoxyethylene based detergents. Compared with Brij 35, Triton X-100 is used more frequently for the solubilization of proteins and lipids. In this study, the solubilization of human platelet protein, cholesterol, gamma glutamyltransferase and lactate dehydrogenase in both detergents were compared. Platelets were treated with Triton X-100 and Brij 35 at various concentrations and various time periods. No significant differences were observed between the detergents at various concentrations and incubation times in terms of the solubilization of platelet protein, cholesterol, gamma glutamyltransferase or lactate dehydrogenase.
Keywords: Brij 35; Platelets; Protein solubility; Triton X-100